Acute changes in glenohumeral range-of-motion following in-season minor league pitching starts. Issue 4 (2nd October 2015) - Case, Jordan M.; Mannava, Sandeep; Fallin, Joshua H.; Stone, Austin V.; Freehill, Michael T.
Abstract: Background. Asymmetric glenohumeral range-of-motion (ROM) between the throwing and non-throwing arms of overhead athletes has been well described in the literature. Thresholds of internal rotation (IR) loss have been associated with throwing arm injury in baseball players. Acute changes in shoulder ROM following an individual pitching appearance remain poorly understood. Objectives: To determine the acute change of external rotation (ER), IR, and total arc-of-motion (TAM) in minor league starting pitchers immediately following an in-season starting pitching appearance. Methods. Nine minor league starting pitchers participated in the study with data collected for 22 individual starts. IR, ER and TAM were measured in the throwing shoulder and non-throwing shoulder at three time points for each appearance: before, immediately following, and at 24 hours following the pitching appearance. Results. In the throwing arm, IR significantly decreased (49.4 vs 46.0, p = 0.037) immediately after pitching, and ER significantly increased immediately following an appearance (150.7 vs 153.6, p = 0.030) and at 24 hours (150.7 vs 154.0, p = 0.028). No difference was detected in throwing arm TAM and IR at 24 hours, or TAM immediately following an appearance. Conclusions. Minor league pitchers demonstrate the dynamic glenohumeral ROM changes after starting appearances of increased ER and diminished IR with maintenance of TAM. At 24 hours, the observed loss of IR had resolved, whereas the gains in ER remained present. Our study supports the need to further assess the acute changes of glenohumeral ROM in pitchers, and the association of acute glenohumeral ROM change with the development of pathologic ROM profiles and injury.